2007
DOI: 10.1073/pnas.0701829104
|View full text |Cite
|
Sign up to set email alerts
|

In vitroerythropoiesis from bone marrow-derived progenitors provides a physiological assay for toxic and mutagenic compounds

Abstract: The goal of this study was to create an in vitro cell culture system that captures essential features of the in vivo erythroid micronucleus (MN) genotoxicity assay, thus enabling increased throughput and controlled studies of the hematopoietic DNA damage response. We show that adult bone marrow (BM) cultures respond to erythropoietin, the principal hormone that stimulates erythropoiesis, with physiological erythropoietic proliferation, differentiation, and enucleation. We then show that this in vitro erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…40,41 PGC-1a was forcibly expressed in Lin -BM cells by infection with a PGC-1a-expressing adenovirus (Ad-PGC-1a) ( Figure 7C-D). After several days, the cells were examined for mRNA expression of the globin genes.…”
Section: To Test This Hypothesis We Isolated Linmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 PGC-1a was forcibly expressed in Lin -BM cells by infection with a PGC-1a-expressing adenovirus (Ad-PGC-1a) ( Figure 7C-D). After several days, the cells were examined for mRNA expression of the globin genes.…”
Section: To Test This Hypothesis We Isolated Linmentioning
confidence: 99%
“…40,41 After 1 day of culture, Lin -cells were infected with an adenovirus that expressed PGC-1a (Ad-PGC1a) or GFP (Ad-GFP) as a control. 42 Infected cells were harvested at the indicated times for QRT-PCR, western blot, and flow cytometric analyses.…”
Section: Cell Culture and Virus Infectionmentioning
confidence: 99%
“…[11][12][13] Compared to the controls, the lineage-negative cells from mDia2 fl/fl Mx-Cre mice showed significantly decreased proliferation, differentiation, and enucleation (Online Supplementary Figure S3A, S3B, and S3C, respectively). Morphologic analysis of the erythroid cells with loss of mDia2 revealed frequent binucleated and enucleating cells (Online Supplementary Figure S3D), further confirming the in vivo assays and the cell-autonomous defects.…”
mentioning
confidence: 99%
“…20 We found that compound depletion of TR2 and TR4 led to a substantial increase of ey-and bh1-globin transcripts (3.6-and 8.2-fold, respectively). Furthermore, the loss of TR2/TR4 resulted in blocking the differentiation, and impairing the maturation, of erythroid cells as anticipated from an earlier RNA sequencing (RNA-seq) analysis showing that the majority of genes affected by TR4 loss of function are intimately linked to vital cellular metabolic functions, 21 indicating that TR2/TR4 are required for erythroid cell survival.…”
Section: Introductionmentioning
confidence: 93%
“…16,24 Murine Lin 2 BM cells were cultured and induced to undergo terminal erythroid differentiation. 20,25 After 1 day of culture, Lin 2 cells were infected with an adenovirus that expressed Cre recombinase (Ad-Cre). After 48 hours, the cells were reinfected.…”
Section: Human Cd34mentioning
confidence: 99%